Nurses’ Job Satisfaction and Organizational Citizenship Behavior in a Regional Hospital: A Cross-Sectional Study - Shiva Maulidia; Masunatul Ubudiyah; Nurul Hikmatul Qowi (Universitas Airlangga, 2026)
Introduction: Organizational Citizenship Behavior (OCB) among nurses plays a crucial role in improving hospital performance, service quality, and patient outcomes. OCB refers to voluntary, extra-role behaviors that go beyond formal job requirements and contribute to organizational effectiveness. Although job satisfaction is often identified as a key predictor of OCB, empirical findings remain inconsistent across different healthcare settings. This study aimed to examine the association between nurses’ job satisfaction and Organizational Citizenship Behavior at Ngimbang Regional Hospital, Indonesia. Methods: A cross-sectional study design was applied. A total of 81 nurses were recruited through purposive sampling based on predefined inclusion criteria, including actively working nurses who consented to participate in the study. Nurses who were on leave or had participated in the preliminary study were excluded. Job satisfaction and OCB were measured using structured questionnaires adapted from validated instruments, each consisting of five key indicators. Data were analyzed using the Spearman Rho correlation test with a significance level set at p < 0.05. Results: The findings indicated that 61.7% of nurses reported high levels of job satisfaction, while 50.6% demonstrated high levels of OCB. Statistical analysis revealed a significant and strong positive correlation between job satisfaction and OCB (p < 0.001; rₛ = 0.602). Conclusion: Nurses’ job satisfaction is significantly associated with Organizational Citizenship Behavior. Enhancing job satisfaction through equitable reward systems, compensation aligned with responsibilities, and supportive work environments may foster positive discretionary behaviors and strengthen overall hospital performance and service quality.